A Study of Activity Models Consistent with Volunteer Activities of Students at Yala Rajabhat University - เจ๊ะแน , นูรอากีฬาสาฟีกา; วาเต๊ะ, นาซูฮา; สะเตาะ , นูห์รอ; มะเกะ, อารีฟ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: 1) examine activity patterns aligned with the volunteer spirit activities of students at Yala Rajabhat University; 2) investigate guidelines for developing activity patterns consistent with students' volunteer spirit; and 3) propose activity patterns that correspond to volunteer spirit activities of students at Yala Rajabhat University. A quantitative research approach was employed. The sample consisted of 382 students from Yala Rajabhat University in the academic year 2025, drawn from a total population of 8,059 students across five faculties, using proportional stratified random sampling. The research instrument was a five-point Likert scale questionnaire, and data were analyzed using descriptive statistics.           The findings revealed as follows. Regarding the first objective, the overall volunteer spirit activity patterns were at a low level (= 2.51). Dimensions rated at a moderate level were: alignment with volunteer spirit principles (= 2.75), opportunities for participation (= 2.65), and activity selection based on personal interest (= 2.61), while the majority of dimensions-including voluntary participation, activity flexibility, time allocation, and post-activity reflection-were rated at a low level (= 2.27). Regarding the second objective, key development guidelines included promoting voluntariness as the foundation of activities, increasing flexibility and diversity of activity options, adjusting scheduling to fit students' academic contexts, and establishing a concrete feedback mechanism following each activity. Regarding the third objective, recommended activity models included transitioning from mandatory participation to a voluntary hour-accumulation system, enabling students to participate in activity design and evaluation, and systematically incorporating post-activity reflection sessions. These measures are intended to effectively and sustainably promote student engagement and the cultivation of public-mindedness.